2022
DOI: 10.1177/10760296221082992
|View full text |Cite
|
Sign up to set email alerts
|

Regression Analysis to Estimate the Factor VIII Activity of Patients with Hemophilia A Without Inhibitor who Received Emicizumab Therapy

Abstract: Background  Emicizumab, a bispecific monoclonal antibody for hemophilia A (HA), has strong pharmacodynamic effects in several coagulation assays resulting in dosing difficulties with Factor VIII (FVIII) concentrates during bleeding emergencies. Materials and Methods Single and multiple regression models were studied to estimate FVIII activity using 27 archived plasma samples from three patients with HA without inhibitor under emicizumab treatment. Explanatory variables were FVIII chromogenic assay (CSA), Ad|mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…73 Another study using modified clot waveform analysis (CWA) showed the equivalent FVIII activity of ~15 IU/dL of emicizumab during the maintenance phase of treatment. 74…”
Section: Section 1: General Considerationsmentioning
confidence: 99%
“…73 Another study using modified clot waveform analysis (CWA) showed the equivalent FVIII activity of ~15 IU/dL of emicizumab during the maintenance phase of treatment. 74…”
Section: Section 1: General Considerationsmentioning
confidence: 99%
“…Some trials have comprehensively used CWA to predict hemostatic effects in emicizumab prophylaxis. 7,18,19 Further, CWA can be used to obtain specific parameters even in infections without disseminated intravascular coagulation (DIC), to distinguish bacterial or viral infection and facilitate selection and early administration of optimal antibiotics for each infection 20 ; moreover, CWA has been associated with the diagnosis of COVID-19, pathological conditions, and prognosis prediction. 21,22 CWA can reflect the entire process of clot formation and is expected to be clinically applied for the differential diagnosis of diseases, severity determination, prognosis prediction, and treatment monitoring in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials have comprehensively used CWA to predict hemostatic effects in emicizumab prophylaxis. 7,17,18 Further, CWA can be used to obtain specific parameters even in infections without disseminated intravascular coagulation (DIC), to distinguish bacterial or viral infection and facilitate selection and early administration of optimal antibiotics for each infection 19 ; moreover, CWA has been associated with the diagnosis of COVID-19, pathological conditions, and prognosis prediction. 20,21 CWA can reflect the entire process of clot formation and is expected to be clinically applied for the differential diagnosis of diseases, severity determination, prognosis prediction, and treatment monitoring in the future.…”
Section: Discussionmentioning
confidence: 99%